Frequency Stabilization of Two Area Power System Interconnected by AC/DC Links using Jaya Algorithm - Tarek Hassan Mohamed, Hussein Abubakr, Mahmoud M. Hussein (International Journal of Advanced Science and Technology, 2020)
This paper presents an application of Jaya based load frequency controller for optimization with the parallel AC/DC of a two area interconnected power system. When an interconnected AC power system undergoes a rapid and large change in loads, system frequency may become oscillatory. A DC link and the existing AC tie line are connected in parallel to stabilize oscillations in frequency. The selection of the optimum controller should not only work in stabilizing the power system for regulation the frequency but also diminish the oscillations in power of the tie line. In common, proportional plus integral (PI) controllers have utilized for load frequency control (LFC) but it unable to eliminate the struggle between the dynamic and static accuracy. This dispute can be resolved by using the principles of Jaya with parallel AC/DC links. For this reason, the parameters of PI-controller have on-line tuned by Jaya algorithm in the presence of the Parallel AC/DC link. The proposed system has examined in case of 20% step load perturbation and the integration of hybrid plug-in electric vehicles (EVs). Simulation results affirmed that the system performance using the proposed design has significantly enhanced as compared to AC/AC and AC/DC links without Jaya. In addition, the suggested system is more vigorous and robust under distinctive operating modes.